Within‐subject reliability of brain networks during advanced meditation: An intensively sampled 7 Tesla MRI case study - Ganesan, Saampras; Yang, Winson F. Z.; Chowdhury, Avijit; Zalesky, Andrew; Sacchet, Matthew D. (Human brain mapping, 2024)
Advanced meditation such as jhana meditation can produce various altered states of consciousness (jhanas) and cultivate rewarding psychological qualities including joy, peace, compassion, and attentional stability. Mapping the neurobiological substrates of jhana meditation can inform the development and application of advanced meditation to enhance well‐being. Only two prior studies have attempted to investigate the neural correlates of jhana meditation, and the rarity of adept practitioners has largely restricted the size and extent of these studies. Therefore, examining the consistency and reliability of observed brain responses associated with jhana meditation can be valuable. In this study, we aimed to characterize functional magnetic resonance imaging (fMRI) reliability within a single subject over repeated runs in canonical brain networks during jhana meditation performed by an adept practitioner over 5 days (27 fMRI runs) inside an ultra‐high field 7 Tesla MRI scanner. We found that thalamus and several cortical networks, that is, the somatomotor, limbic, default‐mode, control, and temporo‐parietal, demonstrated good within‐subject reliability across all jhanas. Additionally, we found that several other relevant brain networks (e.g., attention, salience) showed noticeable increases in reliability when fMRI measurements were adjusted for variability in self‐reported phenomenology related to jhana meditation. Overall, we present a preliminary template of reliable brain areas likely underpinning core neurocognitive elements of jhana meditation, and highlight the utility of neurophenomenological experimental designs for better characterizing neuronal variability associated with advanced meditative states. Graphical illustration of the most reliable brain areas associated with advanced and rare meditation states, called jhanas, determined from an intensively sampled 7 T functional magnetic resonance imaging (fMRI) dataset, using an approach of intraclass correlation modified for estimating within‐subject fMRI reliability at the level of canonical brain networks.